SPEECH ACTS: LOCUTIONARY ACTS USED IN GNOMEO AND JULIET’S FILM - RANI RAKASIWI (LP2MTBM MAKARIOZ, 2019)
This study deals with speech acts used in film. The objectives of this research were to find out the types of locutionary acts used in Gnomeo and Juliet’s Film. Descriptive qualitative method was applied in this study. After collecting the data, then the data was classified and analyzed based on the subcategories of locutionary acts. The results of this research shows The use of the types of locutionary acts in Gnomeo and Juliet’s Film are Phonetic Acts with the total number of 5 utterences or 21.73%; Phatic Acts with the total number of 18 utterences or 78.27%; Rhetic Acts with the total number of none.